BEBAN GANDA PEREMPUAN YANG BEKERJA AKIBAT BIAS GENDER DALAM UU PERKAWINAN - Ni Wayan Merda Surya Dewi (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
The purpose of this study is to investigate the problem of double burden experienced by working women due to gender bias in Marriage Law No. 1 of 1974. This study uses a normative legal method with a statute approach. The study shows that comprehensive legal review is needed regarding the fulfillment of justice for men and women and the relevance of certain articles in the Marriage Law, particularly Article 34, in the context of modern Indonesian society in the 21st century. The gender-biased regulation of Marriage Law implies a double burden that working women must bear in their daily lives. This is because working women are required to do work as housewives (domestic-reproductive) and workers (public-productive) for unlimited hours and with heavy burdens